Enhancing the cultural awareness of Japanese students through virtual exchange: Providing diverse, inclusive, and equitable education - Matsumoto, Yoko (Journal of International Students, 2026)
This paper examines Project Ibunka, a subject-specific virtual exchange program that connects Japanese university students with peers in multiple countries through asynchronous, essay-based written exchanges on politically and socially sensitive issues. Using a mixed-methods design, the study employed the Cultural Intelligence Scale (CQS) alongside follow-up semistructured interviews. The quantitative analysis indicated a significant increase in participants’ metacognitive cultural intelligence. The qualitative findings further suggest that engagement with firsthand narratives and sustained written dialogue encouraged participants to reflect critically on their assumptions, perspectives, and social positioning.